Analisis Kinerja Simpang Bersinyal Pada Simpang PLN Di Wua-Wua Kota Kendari - Saputra, Arsum Rheza Djaya; Lakawa, Irwan; Rachmat, La Ode Musa (Sultra Civil Engineering Journal (SCiEJ), 2020)
This study aims to analyze the degree of saturation of the signaled intersection at the intersection of PLN Wua-Wua Kendari, the long queue condition based on the Manual Capacity Road Indonesia (MKJI, 1997) method with direct measurement in the field, traffic delay condition, and predict the performance of PLN intersection Wua- Wua at 5 and 10 years to come. Data analysis techniques use mathematical equations by using Manual Capacity Method of Indonesia (MKJI, 1997) with the help of Microsoft Excel. Traffic volume surveys and queue lengths are carried out together for 15 minutes each time for 12 hours of measurement. The long queuing condition based on MKJI 1997 method on the east approaches 42,62 meters, west approach 79,5 meter, North approach 47,1 meter and Southern approach 52,4 meter with average queue length 55, 4 meters. While based on the calculation directly in the field obtained value on the approach of the East of 33.51 meters, Western approach of 39.23 meters, Northern approach of 41.53 meters, South approach of 58.05 meters, with an average queue length of 43, 08 meters. The traffic delay on the Eastern approach was 56.2 seconds / smp, Western approach of 84.1 seconds / smp, North approach of 64.1 seconds / smp, and Southern approach of 69.0 seconds / smp. Predicted traffic volume for the next 5 years for the Eastern approach of the DS value of 0.94 with the LOS E, the western approach to the DS value of 1.29 with the LOS F, the North approaches the DS value of 1.20 with the LOS F, the Southern approach of the DS value of 1.27 with LOS F, while for the next 10 years on the Eastern approach the value of DS is 1.57 with LOS F, Western approach of DS value of 2.25 with LOS F, North approach of DS value of 2.00 with LOS F, South DS value of 2.12 with LOS F.